Unilateral open extravesical ureteral reimplanation with contralateral dextronomer/hyaluronic acid injection performed as an outpatient therapy. Issue 6 (December 2018) - Lau, G.; Anderson, R.; Cartwright, P.; Wallis, M.C.; Schaeffer, A.; Oottamasathien, S.; Snow, B.
Summary: Introduction: Historically, patients with unilateral high-grade vesicoureteral reflux (VUR) and contralateral low-grade or resolved VUR have been treated with bilateral intravesical ureteral reimplantation, which requires postoperative admission. If the high-grade VUR side is treated alone, then the contralateral side is at risk of developing recurrent or worsening VUR. Bilateral subureteric injection of dextronomer/hyaluronic acid (DHA) is another option that can be performed as an outpatient therapy, but a single injection is less effective for high-grade VUR. Objective: The safety and efficacy of an outpatient combination of open extravesical ureteral reimplantation (EVUR) and contralateral DHA injection were investigated. Study design: A retrospective review of children who had concomitant EVUR and subureteric injection of DHA between January 2005 and December 2015 was performed. Exclusion criteria were diagnosis other than VUR, repeat procedures, and patients with no follow-up. Patient characteristics, postsurgical complications, and follow-up imaging were evaluated. Febrile urinary tract infection (fUTI) was defined as ≥50, 000 Colony Forming Units (CFU) of an organism from clean-catch or catheterized urine and temperature ≥ 101.5 F. Clinical success is defined as no fUTI for 1 year after the initial operation. Univariate analyses were used to identify risk factors for treatment failure. Results: A total of 117 patients met inclusion criteria. Mean age at surgery was 6.0 years, and 85% were female. The mean pre-operative grade of VUR was 3.3 on the EVUR side and 0.6 on the contralateral side (42% resolved before treatment). Median follow-up was 12.2 months (interquartile range, 3.1–25.4). Sixteen patients (14%) had documented fUTI within 1 year, with a clinical success rate of 86%. Of these, five had a postoperative imaging showing resolution of VUR, increasing overall success to 91%. Postoperative fUTI was more common in patients with pre-operative bowel and bladder dysfunction (BBD) ( P  = 0.003), but this was not associated with a higher reoperation rate ( P  = 0.168). There were 11 total complications, with three grade 3 complications. Discussion: This study is the first to report safety and outcomes of EVUR and contralateral DHA injection for patients with high-grade VUR with contralateral low-grade or resolved VUR. It was shown that it is an effective and safe treatment that can be performed as an outpatient therapy. Limitations to this study include the retrospective design and the clinical definition of success that is used in a cohort of patients from across the mountain west region without routine postoperative voiding cystourethrogram. Conclusion: Extravesical ureteral reimplantation and contralateral DHA injection can safely be performed as an outpatient therapy and are effective in the treatment of higher grade VUR with contralateral low-grade or resolved VUR. Treatment failure is more likely in patients with BBD.